2018
DOI: 10.1111/and.13205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of orchiectomy on sperm functional aspects and semen oxidative stress in men with testicular tumours

Abstract: To verify if quality of spermatozoa from men with testicular germ cell tumours is better before or after orchiectomy. This prospective study was carried out including 24 patients with testicular germ cell tumours, who provide one semen sample before they were submitted to unilateral orchiectomy and one other semen sample 30 days after the surgery. After collection by masturbation and liquefaction, an aliquot of the semen sample was used for semen analysis and another was used to evaluate sperm mitochondrial ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…The adjuvant treatment utilization is common; thus, a high rate of patients will become azoospermic (10 to 24%) (31). Andrade et al (2019) investigated the semen quality of patients before and after orchiectomy, and in both groups, there was a decrease in ejaculated volume (54.2%) and sperm concentration (50.0%), motility (50.0%) and morphology (20.8%), but it is necessary to consider the low sample size used (total of 24 men: 15 with seminoma tumor and 9 with non-seminoma tumor) (32).…”
Section: Tgcts and Fertility Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…The adjuvant treatment utilization is common; thus, a high rate of patients will become azoospermic (10 to 24%) (31). Andrade et al (2019) investigated the semen quality of patients before and after orchiectomy, and in both groups, there was a decrease in ejaculated volume (54.2%) and sperm concentration (50.0%), motility (50.0%) and morphology (20.8%), but it is necessary to consider the low sample size used (total of 24 men: 15 with seminoma tumor and 9 with non-seminoma tumor) (32).…”
Section: Tgcts and Fertility Potentialmentioning
confidence: 99%
“…Therefore, it is recommended that these patients receive a correct medical advice in order to preserve their fertility for a future parenthood (31). Thus, patients who wants to attain parenthood should be advised to adhere to semen cryopreservation for its later use in assisted reproduction techniques (32).…”
Section: Tgcts and Fertility Potentialmentioning
confidence: 99%
“…Regarding the DNA damage pathway, a difference was observed when comparing pre‐ and post‐orchiectomy groups with the control group. Accordingly, in a previous study, we have demonstrated a decrease in sperm DNA fragmentation after orchiectomy (Andrade et al., 2019). DNA damage and repair is constant in all living cells, once this damage can normally take place as a result of cellular respiration and metabolism (both normal and aberrant).…”
Section: Discussionmentioning
confidence: 58%
“…Our group has already studied proteins in seminal plasma of men with different conditions that may affect male fertile potential, demonstrating that this fluid is capable of detecting intratesticular alterations (Antoniassi et al., 2016; Belardin, Camargo et al., 2019; Belardin et al., 2016, 2019; Camargo et al., 2013, 2019; Intasqui et al, 2018; Intasqui, et al, 2015; Intasqui et al, 2013a; Intasqui et al, 2013b; Intasqui, et al., 2015). Furthermore, once we have observed alterations in sperm function of men with testicular germ cell tumours (Andrade et al., 2019), we hypothesised that testicular tumours may also alter testicular proteomic pathways related to apoptosis and DNA damage, reflecting in detectable different levels of these proteins in seminal plasma. To attest our hypothesis, we aimed to verify in seminal plasma, by a multiplex approach, DNA damage and apoptosis pathways in men without testicular tumours (control) and pre‐ and post‐unilateral orchiectomy, for TGCT removal.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation